TO BE A SUCCESSFUL FOREIGN LANGUAGE LEARNER; REFLECTING FROM CHILDREN - Basuni, Muh. (Pusat Pengembangan Bahasa IAIN Tulungagung, 2011)
Learning a foreign language has haunted many adult learners since it is considered very difficult. Looking at the childhood period, everybody has been successfully through his first language learning process. Therefore, every foreign language learner can revival their childhood victory in learning language simply by recurring their strategies in learning a foreign language. This article offers a foreign language learner, in this case English, a strategy by imitating the way young children learn their first language.